2018
DOI: 10.1186/s13293-018-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in discontinuation of statin treatment in women and men with advanced cancer disease

Abstract: BackgroundStatins are often discontinued in patients with advanced cancer since the net effect of treatment is considered negative. However, guidelines concerning discontinuation of statin treatment are lacking. The aim of this study was to investigate any differences in time of discontinuation of statin treatment between men and women with advanced cancer disease.MethodsMedical records from 195 deceased palliative cancer patients from a previous study cohort were reviewed. Patients treated with statins 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
4
3
0
Order By: Relevance
“…The results from this study, is in concordance with our previous, smaller study, which showed that statins were discontinued earlier in women than in men [ 18 ]. However, in that study patients with advanced cancer two years before death were included and they followed for the two last years in life compared to the last year in life in this study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results from this study, is in concordance with our previous, smaller study, which showed that statins were discontinued earlier in women than in men [ 18 ]. However, in that study patients with advanced cancer two years before death were included and they followed for the two last years in life compared to the last year in life in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, there was no difference in cardiovascular events or cardiovascular mortality between men and women after statin discontinuation. This is also in line with earlier studies showing that statin discontinuation in palliative care patients do not affect mortality or cardiovascular events [ 12 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations